The effects of population density on the breeding performance of mountain hare Lepus timidus. Issue 4 (1st December 2013) - Knipe, Annabel; Fowler, Paul A.; Ramsay, Scot; Haydon, Daniel T.; McNeilly, Alan S.; Thirgood, Simon; Newey, Scott
Abstract : Feedback between population density and demographic parameters often plays a determining role in population dynamics, and it is particularly important in managing exploited or harvested populations. The mountain hare Lepus timidus is a traditional game species, which is hunted in Scotland for sport and population control. However, information about how population parameters respond to changes in population density is lacking. To assess how reproduction and juvenile recruitment change in response to population density, we sampled 189 hares (88 females and 101 males) from 10 independent private hunting estates. We found a significant negative correlation between population density and the proportion of juveniles recruited into the breeding population, along with a significant interaction between population density and sex, which revealed that the proportion of juvenile females recruited decreases more rapidly with population density compared to the proportion of male juveniles. However, we found no evidence of density‐dependent fecundity. Our results suggest density‐dependent compensation in this species, acting on recruitment, not fecundity, with rates of juvenile recruitment differing between the sexes. We conclude that the significant correlation between population density and juvenile recruitment may provide harvested populations with the potential for compensatory juvenile recruitment, although harvesting rates need to be accurately estimated to avoid the risk of overharvesting.